Crystallographic identification of an unusual homoleptic palladium citrate [Na(OH2)6]·{[Na3(OH2) 8]3[NaPd3(C6H4O 7)3]2}·(H2O) stabilised by intermetallic aggregation with sodium and heavy hydration - Gunari, P. (2014)
10.1039/c0dt00273a